Factors Contributing to EFL Learners’ Construction of Arguments in Culturally Infused Discussions - Pablo Vergara-Montes; Luzkarime Calle-Díaz (HOW, 2024)
This study describes the factors that enhanced students’ construction of arguments when participating in culturally infused discussions at an undergraduate English as a foreign language British Culture course. The research was conducted at a university in Northwestern Colombia. This paper presents a section of the results of a larger project whose objective is to identify the elements that aid participants in building and elaborating arguments in culturally infused discussions. Socratic questioning was an integral element of the discussions. To attain the purpose of this study, a qualitative single-case design was employed. Findings show that the factors facilitating the construction of arguments could potentially be peer scaffolding, previous knowledge, connection to participants’ reality, and curiosity and inquiry. This study makes important contributions to the field of critical thinking skills work in English as a foreign language setting, particularly argumentation, as it sheds light on relevant aspects to foster students’ collaborative argumentation.